Aksesibilitas Ibadah bagi Tunanetra: Pengembangan Teknologi Asistif Berbasis Artificial Intelligence dalam Perspektif Fikih - Eko Julianto Wibowo; Ngainun Naim (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2025)
The emergence of artificial intelligence (AI) technology has opened up exciting new horizons in the field of Islamic law including visually impaired people. Thanks to its ability to process data quickly and in a structured manner, AI is seen as a potential instrument to support the legal deduction process. However, the use of AI in the realm of legal decision making is not simple. There are fundamental ethical and epistemological problems, because these digital devices do not have fiqh intuition, a moral compass, let alone a deep understanding of maqāṣid al-syarī‘ah. This study uses qualitative research through a literature review. This study tries to dissect the position of AI in the view of the consensus (ijma') of ulama and its relevance to current innovation trends. Based on the analysis carried out, an agreement was found among ulama that AI should be positioned as a mere analytical tool that remains under the control of sharia experts. Even though AI is very superior in speeding up reference searches and mapping arguments from classical texts, the authority of a mujtahid in establishing laws cannot be replaced by machines. This research emphasizes that the main key to utilizing AI lies in ethical management and strict regulations. Collaboration between technology developers and religious institutions is very crucial in ensuring that the use of this technology remains within the corridors of sharia. In the end, AI integration that is in line with the principles of maqāṣid al-syarī'ah is expected to be able to bring benefits to the people without eroding the integrity and noble values ​​of Islamic law itself.